Adsorption Kinetics and Isotherm of Crystal Violet by Carbon Modified with Magnetite (Fe3O4) and Triethoxyphenylsilane (TEPS) from Rubber Fruit Shell - Nadya Syarifatul Fajriyah; Buhani Buhani; Suharso Suharso (Indonesian Journal of Chemistry, 2023)
Rubber fruit shells-derived carbon (RC) modified with magnetite (MRC) and triethoxyphenylsilane (TEPS) (SRC) made from rubber fruit shells were used to adsorb crystal violet (CV) dye effectively. The RC was successfully modified by magnetite and TEPS, according to the characterization of the adsorbent utilizing Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD), and scanning electron microscopy-energy-dispersive X-ray (SEM-EDX) showed that the RC was successfully modified by magnetite and TEPS. Several adsorption process parameters were investigated, and the ideal results were obtained with an adsorbent dose of 0.1 g, pH 10, contact time of 15 min, and initial concentration of CV 250 mg L−1. The MRC and SRC adsorption capacities are 71.43 and 69.93 mg g−1, respectively. The adsorption kinetics followed a pseudo-second-order model with MRC and SRC rate constants of 3.40 and 0.83 g mg−1 min−1, respectively. The Freundlich adsorption isotherm is suitable for CV dye adsorption using MRC and SRC with KF values are 1.36 and 1.76 mg g−1 L mg−1 which gives R2 0.943 and 0.932, respectively. These findings showed that the modified RC with magnetite and TEPS effectively removes the CV dye solution through the adsorption process.